Territorial disparity index: a GIS-integrated data framework for territorial disparities measurement in rural Morocco - Nassima Tabloul; Mohcine Kodad; Mimoun Boukhidous; El Houcine Addou (Bulletin of Electrical Engineering and Informatics, 2026)
Despite availability of numerous indicators for territorial evaluation and the measurement of their deprivation or advantage, the results remain confined to a coarse-grained spatial scale and cannot be applied at finer levels of territories like to Moroccan rural entities known as douars. This paper presents a bottom-up framework termed territorial disparity index (TDI) that quantitatively conceptualize territories as entities shaped through data-driven technological processes in order to better control and develop them and above all to reduce their multi-scale disparities. Through this study, we propose a geographic information system (GIS)-integrated data for composite index through two key dimensions: socio-economic and spatial-environmental aspects, quantified as scores based on 32 variables translated into indicators, then converted into decile ranks through a systematic data processing pipeline. The framework of TDI not only enhances spatial sensitivity often overlooked, but also provides a highly objective tool for mapping territorial disparity. Applied to actual data of a real Moroccan territory, in Berkane, this research introduces a novel methodology for territorial data collection, combining cross-sectional and spatial data analysis to digitally perceive these territories according to their levels of disadvantage. Principal component analysis (PCA) is then used to ensure robustness and objectivity of TDI index.